An Overview of Evapotranspiration Guide for Irrigated Crops in Turkey - Melek Yiğen; Murat Tekiner (Turkish Journal of Agriculture: Food Science and Technology)
The “Action Plan for the Water Use in Agriculture Activation Program” in the Tenth Five-Year Development Plan, prepared by The Ministry of Development for the period 2014-2018, is one of the most important indicators of the increasing importance of water resources and irrigation. It’s published according to Blaney-Criddle method with the data of the Crop Evapotranspiration Guideline in 1982, for a guide to be updated by General Directorate of Agricultural Research And Policies (TAGEM) and General Directorate of State Hydraulic Works (DSI) in 2013, using the Food and Agriculture Organization (FAO) Penman Monteith method. While DSİ undertakes the calculation of reference plant water consumption (ET0), effective precipitation and irrigation water requirement of this update, TAGEM is responsible for the compilation of information obtained from irrigation researches, calculation of plant coefficient (kc) values, publication of guides in written and electronic media realized. In this study, five guides (Balıkesir, Çanakkale, Edirne, Kocaeli and Tekirdağ) in three different climatic regions (Akdeniz Ardı, Marmara and İç Geçit-Marmara) were used in this guide, which the two institutions jointly organize and update with intensive effort, TUIK 2012-2016 considering the data, the county made on the basis of agriculture and untreated plants, guide place whether to get cases examined, the importance and aspects to be developed contacts have tried to reveal.